Spatio Temporal Distribution of Anthrax in Sulawesi 2015-2018 - Titis Furi Djatmikowati; Dini Wahyu Yudianingtyas; Haeriah Haeriah (Acta VETERINARIA Indonesiana, 2019)
Three among five Provinces (South Sulawesi, West Sulawesi and Gorontalo) in Sulawesi island, Indonesia are endemic area of anthrax disease. The aim of this study was to describe the dynamic of anthrax during 2015-2018 and identified risk area in Sulawesi. We determined case of anthrax disease from passive-active surveillance data Disease Investigation Center Maros (DIC Maros) during 2015-2018. Spatial distribution describe by mapping using Quantum Geographic Information System (QGIS), the temporal distribution describe using epidemic curve and we calculated the proportion of animal infected of anthrax. There were thirty-three cases of anthrax spreaded into three Provinces in Sulawesi, there were twenty one cases in South Sulawesi (63.6%), nine cases in Gorontalo (27.3%) and three cases West Sulawesi (9.1%). There were eleven cases (33.3%) in 2015, fifteen cases (45.5%) in 2016, four cases (12%) in 2017 and three cases (6%) in 2018. Anthrax occured respectively in dry season in South Sulawesi and Gorontalo, different with West Sulawesi anthrax occured in rainy season. The proportion of the animal infected were 87% in cattle, 7% in horse, 3% goat and 3% in deer. Vaccination of anthrax in South Sulawesi and Gorontalo should be conducted in May; in Polewali Mandar, West Sulawesi in Februari.